Living the Values of Mercy: Moral and Social Development in Indonesian Pesantren through the Yellow Book Tradition - Kodir, Abdul; Shahruddin, Mohd Solahuddin (FOCUS, 2025)
Pesantren, as a traditional Islamic educational institution, not only transfers religious knowledge but also instills moral and social values ​​that are in line with the principles of compassion, justice, and concern for others and the universe. The yellow book, as the main source of learning in pesantren, has a major role in translating the values ​​of Rahmatan Li al-Ālamīn into daily life practices. Through the teaching of fiqh, tasawuf, and other teachings, students not only understand religious theory but are also taught to practice these values ​​in their social interactions. The application of the concept of Rahmatan Li al-Ālamīn is also reflected in social life in pesantren, where students are taught to live together in harmony, help each other, and respect differences. Social activities carried out by pesantren, such as providing assistance to the community, show that this value of compassion applies not only to relationships between individuals but also to relationships with society at large. In addition, literacy in yellow books also makes a big contribution to the development of the character of students, by teaching moral and ethical values ​​that are in line with the principle of Rahmatan Li al-Ālamīn.